Los Valores en Los Consumidores Millennials de la Ciudad de Saltillo, Coahuila - Adriana Méndez Wong; Edith Reyes Ruiz; Jesús Francisco Mellado Siller; Karina Lizbeth Rodriguez Ramirez (European Scientific Journal, ESJ, 2017)
This study makes a descriptive analysis of the clients profiles that belong to the Y or Millenial generation in the city of Saltillo, Coahuila. The study was performed using the Values List Scale (LOV) attributed to Khale (Khale, Beatty, & Homer, 1986) quoted by Irene Ramos Soler (2008). This scale was used for the investigation of market segmentation and in identifying target markets. It is a work that has to do with the field of marketing. This study however is considered as an exploratory, descriptive, quantitative, and transversal investigation. Using Pearson’s chi square analysis and an answer percentage comparison with the IBM SPSS software, they show us that the more important values are self-completion and selfesteem. A stratification sample was used. It also uses age variable and it applies a questionnaire instrument to 261 people that belong to Y generation in Saltillo, Coahuila.